Optimizing Occupational Safety Through 3-D Simulation and Immersive Virtual Reality - Kwegyir-Afful, Ebo; Lindholm, Maria; Tilabi, Sara; Tajudeen, Sulaymon; Kantola, Jussi (Springer, 2019)
This paper evaluates the effectiveness of computer simulation and the immersive virtual reality (IVR) technology for occupational risk assessment improvement. It achieves this by conducting a risk assessment on a 3-D simulation of a Lithium-Ion battery (LIB) manufacturing factory. This is necessary since calls for the enhancement of occupational risk assessments continue to dominate safety improvement measures in manufacturing context. Meanwhile, industries such as aviation, mining and healthcare employ advanced versions of IVR for risks awareness with successes. However, applications for safety in manufacturing context is only at the infancy although it utilizes IVR profitably for product and production optimization issues. The study involved 19 participants who performed the assessment with the aid of a safety checklist followed by open-ended semi-structured questions and interviews. Results indicates an outstanding utilization capability of IVR for risk assessment. Furthermore, the assessment pinpoints specific safety issues in the factory that requires attention and improvement.
Keywords: 3-D simulation; hazard identification; immersive visual reality; manufacturing industry; risk assessment; fi=Tuotantotalous|en=Industrial Management|